Bokanmälan: Relating practices and research in mathematics education - Helenius, Ola (NOMAD Nordic Studies in Mathematics Education, 2009)
C. Bergsten, B. Grevholm, H. Strømskag Måsøval & F. Rønning (red.) (2007). Relating practices and research in mathematics education. Proceedings of NORMA 05, fourth Nordic conference on mathematics education. Trondheim: Tapir Academic Press. ISBN 978-82-519-2212-8